Paisajes de aprendizaje en la enseñanza de las Ciencias Naturales - Chávez Guerrero, Andrea Mishell (2025)
This research analyzes how learning landscapes support the teaching of Natural Sciences at the Intermediate level of Basic Education. The study uses a mixed-methods approach. It combines qualitative and quantitative techniques in a non-experimental design. Observation and surveys were used. Instruments included observation checklists and structured questionnaires. Both teachers and students from “San Pablo” Primary School participated. The research begins by exploring educational resources in the Ecuadorian context. There is some openness to active methodologies, but traditional practices persist. Conventional materials like textbooks and workbooks are mainly used. Learning landscapes are digital resources designed with Bloom’s Taxonomy and Multiple Intelligences. They offer innovative, playful activities to teach Natural Sciences. This subject aims to foster curiosity through teacher-guided experimental inquiries. It also supports understanding complex topics through ICT and technology tools. The findings show a need for a guide for designing learning landscapes to support teaching. The goal is to enrich Natural Sciences instruction, boost student motivation, and promote meaningful, inclusive, and contextualized learning.